In Dora's case: Freud, hysteria, feminism - Bernheimer, Charles; Kahane, Claire (Columbia University Press, 1990)
A collection of essays that question Freud's assumptions about femininity and female desire. Several essays situate their critiques within the context of contemporary French writing on psychoanalysis and feminism, while others display the variety and finesse of the interpretive strategies exercised by contemporary feminist critics.
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychanalyse; santé; santé des femmes*; sciences; sexualité; systèmes d'oppressions; thématiques

De l'indécence aux hommes d'accoucher les femmes, et ; De l'obligation aux mères de nourrir leurs enfants, suivi de ; S'il est des signes qui assurent de la puissance des hommes, autant que le font ceux qui répondent de la sagesse des filles 1707 - Hecquet, Philippe (Côté-femmes, 1990)
Première publication 1744
Keywords: 1700-1799; cours; discipline; europe; fem1000; france; histoire; premier cycle; périodes historiques; régions géographiques; santé; santé reproductive; sciences humaines; thématiques

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis